The Future of Transport Between Digitalization and Decarbonization : Trends, Strategies and Effects on Energy Consumption /: Trends, Strategies and Effects on Energy Consumption. (2020) - Noussan, Michel; Hafner, Manfred; Tagliapietra, Simone
No abstract available